The Influence of Electronic Word of Mouth, Service Quality, and Cafe Atmosphere on Purchasing Decisions at Zozo Garden Coffeeshop - Ningsih, Rima; Rinova, Dora (Indonesian Journal Publisher, 2025)
This research investigates how Electronic Word of Mouth, Service Quality, and Café Atmosphere influence purchasing decisions at Zozo Garden Coffeeshop in Bandar Lampung City. A quantitative approach with descriptive methods was employed, utilizing purposive sampling to select a sample of 96 respondents. Multiple linear regression analysis was used to process the data. Results from the t-test indicate that Electronic Word of Mouth significantly impacts purchasing decisions at Zozo Garden Coffeeshop. Likewise, Service Quality and Café Atmosphere also significantly affect purchasing decisions. The R Square value of 0.708 from the coefficient of determination test suggests that these three variables explain 70.8% of purchasing decisions, with the remaining 29.2% attributable to other factors outside the study's scope.